TINGKAT KERAMAHAN DALAM KOMUNIKASI KARYAWAN RESTORAN BAKMI SEBAGAI PENUNJANG KUALITAS PELAYANAN - Kuncoro Dewi Rahmawati; Imanuel Deny Krisna Aji (Jurnal Ilmu Komunikasi AKRAB, 2019)
The service quality felt by customers can be demonstrated even from the first timethe customer enters the restaurant area. This is the main key for customers to begin toassess whether the service in the destination restaurant is in accordance with service qualitystandards or not. As the culinary business grows, of course the owners must pay attention tothe quality of services so they don't compete. One of the developing culinary restaurants,Noodles X is one of the business people who helped enliven the Indonesian culinary market.The focus of this study is choosing aspects of hospitality, the selection of aspects ofhospitality is considered the first communication pattern received by customers, even whenentering the restaurant area. The method used in this study is observation. The observationdesign used is natural setting, participant observation and the method of recording using arating scale. The choice of using the rating scale method because of the observed behavior,researchers want to know the degree of quality of the behavior itself. Implementation ofobservations is divided into 30 days, with the calculation of the average results ofobservations at the weekend and the average observation results on weekday. Based onobservations made, it can be concluded that the level of friendliness in the communicationpractices of restaurant noodle employees is included in the class "very well". There areinteresting findings between the acquisition of friendliness level scores on weekdays and onweekends. The average score obtained from the five highest indicators is on weekends